The Role of Real Earnings Management (REM) in The Relationship between Financial Distress and Tax Planning - Souisa, Angeline Grece; Tjondro, Elisa; Kusumawardhani, Adhityawati; Sadjiarto, Arja; Eoh, Tonny Stephanus (Accounting Department, School of Business and Management - Universitas Kristen Petra, 2024)
The aim of this study is to test the impact of real earnings management (REM) on the relationship between financial distress and tax planning. To survive and maximise financial potential in the face of financial distress, management tends to use accounting tactics to increase revenue in order to reach the company's target. The study sample comprises manufacturing sector firms listed in the IDX between 2018 and 2022. The total company sample consisted of 124 companies with 542 observations. The study employed robust random effect panel regression techniques. This research reveals that there is a negative link between financial distress and tax planning. This study fails to prove that REM strengthens the relationship between financial distress and tax planning. Furthermore, the study discovered that two groups of firms with high and low REM abnormal cash flows exhibited distinct financial distress behaviours towards tax planning. The practical implications are that increased regulatory attention and decreased financial resources create a lower motivation to evade taxes, as exhibited by the negative correlation between financial distress and tax planning.